Caffeine reverts loss of muscular performance during the early-follicular phase in resistance-trained naturally menstruating women - Santana, O.; Vieira-Cavalcante, V.; Caetano Paulo, A.; Rodacki, C.; Bertuzzi, R.; Lima-Silva, A. E.; Cristina-Souza, G. (Journal of Sports Sciences, 2022)
The aim of this study was to compare the effects of caffeine ingestion on muscular performance during the early-follicular and mid-luteal phases of the menstrual cycle. Fourteen resistance-trained naturally menstruating women performed countermovement jump (CMJ), maximal voluntary isometric contraction (MVIC), one-repetition maximum (1-RM), and repetitions-to-failure (RF) at 80% of 1-RM in the half-squat exercise, in early-follicular and mid-luteal phases, after placebo or caffeine ingestion. The early-follicular and mid-luteal phases were identified via calendar-based counting method. The MVIC was lower in the early-follicular than mid-luteal phase (-6.2 ± 15.2 N, p < 0.05) and higher with caffeine than placebo ingestion regardless of the menstrual cycle phase (+16.8 ± 26.7 N, p < 0.05). The magnitude of gains (supplement x phase interaction, p < 0.026) in 1-RM, CMJ, and RF with caffeine ingestion was higher in the early-follicular (+16.6 ± 7.1 kg, +2.5 ± 1.6 cm, and +4.5 ± 2.6 repetitions, respectively) than in the mid-luteal phase (+7.7 ± 4.8 kg, +1.5 ± 2.0 cm, and +2.4 ± 3.1 repetitions, respectively). In conclusion, the greater ergogenic effect of caffeine during the early-follicular phase supports its use to mitigate the decline in muscular performance in this phase of the menstrual cycle.